Recapturing Value Through Reverse Logistics: Wärtsilä Ship Power - shopping list - Ilonen, Tuomo (My University, 2010)
Every now and then Wärtsilä Ship Power faces problems with project cancellations from customer side or incorrect purchase orders. Unless capable of canceling the orders from external suppliers in time, materials are taken to warehouse and to a shopping list. From this list they can be used to a different project. Unfortunately the current process is ineffective and does not bring the savings that it could. Project execution, operative purchasing and business control all have their responsibilities but no dedicated resources appointed. Processes of reselling material back to suppliers or scrapping them don’t exist at all. Shopping list process has defects in the process itself; responsibilities and information sharing is inadequate. Internal marketing of the list is missing. Reverse logistics process in business to business relationship is shortly studied area. I reviewed business process and business process redesigning as well as reverse logistics and relocation options from the literature to get an overview of all possible options to re-create smooth and effective shopping list process. Besides the literature review, I got valuable info from my own work experience inside the supply management department. In my case, reverse logistics process was far from the core processes within Wärtsilä Ship Power. That is why I deemed it necessary to have only one person handling all operative work – the shopping list responsible. Other users of the list, both internal and external of the Ship Power department, need to be considered as customers, although they have some responsibilities in the process. Close cooperation between different functions is needed, especially with strategic purchasers who are in the best position to discuss about selling back the material to external suppliers. No process can work if it is not handled properly. Even a one person can be a good promoter.
Keywords: Business process; Business process redesign; Reverse logistics; Obsolescence; Purchase; fi=Tuotantotalous|en=Industrial Management|